# RD Sharma Class 12 Ex 16.3 Solutions Chapter 16 Tangents and Normals

Here we provide RD Sharma Class 12 Ex 16.3 Solutions Chapter 16 Tangents and Normals for English medium students, Which will very helpful for every student in their exams. Students can download the RD Sharma Class 12 Ex 16.3 Solutions Chapter 16 Tangents and Normals book pdf download. Now you will get step-by-step solutions to each question.

## RD Sharma Class 12 Ex 16.3 Solutions Chapter 16 Tangents and Normals

### (i) y2 = x and x2 = y

Solution:

First curve is y2 = x. . . . . (1)

Differentiating both sides with respect to x, we get,

=> 2y (dy/dx) = 1

=> m1 = dy/dx = 1/2y

Second curve is x2 = y . . . . (2)

Differentiating both sides with respect to x, we get,

=> 2x = dy/dx

=> m2 = dy/dx = 2x

Solving (1) and (2), we get,

=> x4 − x = 0

=> x (x3 − 1) = 0

=> x = 0 or x = 1

We know that the angle of intersection of two curves is given by,

tan θ = where m1 and m2 are the slopes of the curves.

When x = 0, then y = 0.

So, m1 = 1/2y = 1/0 = ∞

m2 = 2x = 2(0) = 0

Therefore, tan θ = = ∞

=> θ = π/2

When x = 1, then y = 1.

So, m1 = 1/2y = 1/2

m2 = 2x = 2(1) = 2

Therefore, tan θ = => θ = tan−1 (3/4)

### (ii) y = x2 and x2 + y2 = 20

Solution:

First curve is y = x2. . . . . (1)

Differentiating both sides with respect to x, we get,

=> (dy/dx) = 2x

=> m1 = dy/dx = 2x

Second curve is x2 + y2 = 20 . . . . (2)

Differentiating both sides with respect to x, we get,

=> 2x + 2y (dy/dx) = 0

=> m2 = dy/dx = −x/y

Solving (1) and (2), we get,

=> y2 +y − 20 = 0

=> y2 + 5y − 4y − 20 = 0

=> (y + 5) (y − 4) = 0

=> y = −5 or y = 4

Ignoring y = − 5 as x becomes √(−5) in that case, which is not possible.

When y = 4, we get x2 = 4

=> x = ±2

We know that the angle of intersection of two curves is given by,

tan θ = where m1 and m2 are the slopes of the curves.

When x = ±2 and y = 4, we get,

m= 2x = 2(2) = 4 or ±4

m2 = −x/y = −2/4 = −1/2

So, tan θ = => θ = tan−1 (9/2)

When x = −2 and y = 4, we get,

m1 = 2x = 4 or −4

m= −x/y = 1/2 or −1/2

So, tan θ = => θ = tan−1 (9/2)

### (iii) 2y2 = x3 and y2 = 32x

Solution:

First curve is 2y2 = x3. . . . . (1)

Differentiating both sides with respect to x, we get,

=> 4y (dy/dx) = 3x2

=> m1 = dy/dx = 3x2/4y

Second curve is y2 = 32x. . . . . (2)

Differentiating both sides with respect to x, we get,

=> 2y (dy/dx) = 32

=> m2 = dy/dx = 32/2y = 16/y

Solving (1) and (2), we get,

=> 2(32x) = x3

=> x3 − 64x = 0

=> x(x2 − 64) = 0

=> x = 0 or x2 − 64 = 0

=> x = 0 or x = ±8

We know that the angle of intersection of two curves is given by,

tan θ = where m1 and m2 are the slopes of the curves.

When x = 0 then y = 0.

m1 = 3x2/4y = ∞

m2 = 16/y = ∞

So, tan θ = ∞

=> θ = π/2

When x = ±8, then y = ±16.

m1 = 3x2/4y = 3 or −3

m2 = 16/y = 1 or −1

So, tan θ = => θ = tan−1 (1/2)

### (iv) x2 + y2 – 4x – 1 = 0 and x2 + y2 – 2y – 9 = 0

Solution:

First curve is x2 + y2 – 4x – 1 = 0. . . . . (1)

Differentiating both sides with respect to x, we get,

=> 2x + 2y (dy/dx) – 4 = 0

=> m1 = dy/dx = (2–x)/y

Second curve is x2 + y2 – 2y – 9 = 0. . . . . (2)

Differentiating both sides with respect to x, we get,

=> 2x + 2y (dy/dx) – 2 (dy/dx) = 0

=> m2 = dy/dx = –x/(y–1)

First curve can be written as,

=> (x – 2)2 + y2 – 5 = 0 . . . . (3)

Subtracting (2) from (1), we get

=> x2 + y2 – 4x – 1 – x2 – y2 + 2y + 9 = 0

=> – 4x – 1 + 2y + 9 = 0

=> 2y = 4x – 8

=> y = 2x – 4

Putting y = 2x – 4 in (1), we get,

=> (x – 2)2 + (2x – 4)2 – 5 = 0

⇒ (x – 2)2(1 + 4) – 5 = 0

⇒ 5(x – 2)2 – 5 = 0

⇒ (x – 2)2 = 1

⇒ x = 3 or x = 1

So, when x = 3 then y = 6 – 4 = 2

m1 = (2–x)/y = (2–3)/2 = –1/2

m2 = –x/(y–1) = –3/(2–1) = –3

So, tan θ = = 1

=> θ = π/4

So, when x = 1 then y = 2 – 4 = – 2

m1 = (2–x)/y = (2–1)/(–2) = –1/2

m2 = –x/(y–1) = –1/(–2–1) = 1/3

So, tan θ = = 1

=> θ = π/4

### (v) x2/a2 + y2/b2 = 1 and x2 + y2 = ab

Solution:

First curve is x2/a2 + y2/b2 = 1 . . . . (1)

Differentiating both sides with respect to x, we get,

=> 2x/a2 + (2y/b2) (dy/dx) = 0

=> m1 = dy/dx = –b2x/a2y

Second curve is x2 + y2 = ab . . . . (2)

Differentiating both sides with respect to x, we get,

=> 2x + 2y (dy/dx) = 0

=> m2 = dy/dx = –2x/2y = –x/y

Solving (1) and (2), we get,

=> x2/a2 + (ab – x2)/b2 = 1

=> x2b2 – a2x2 = a2b2 – a3b

=> x2 = => x = From (2), we get, y2 = => y = So, m1 = –b2x/a2y = = m2 = –x/y = = Therefore, tan θ = => tan θ = => tan θ = => θ = tan–1 ((a–b)/√ab)

### (vi) x2 + 4y2 = 8 and x2 – 2y2 = 2

Solution:

First curve is x2 + 4y2 = 8 . . . . (1)

Differentiating both sides with respect to x, we get,

=> 2x + 8y (dy/dx) = 0

=> m1 = dy/dx = –2x/8y = –x/4y

Second curve is x2 – 2y2 = 2 . . . . (2)

Differentiating both sides with respect to x, we get,

=> 2x – 4y (dy/dx) = 0

=> m2 = dy/dx = x/2y

Solving (1) and (2), we get,

6y2 = 6 => y2 = ±1

x2 = 2 + 2 => x = ±2

So, tan θ = => θ = tan–1 (1/3)

### (vii) x2 = 27y and y2 = 8x

Solution:

First curve is x2 = 27y . . . . (1)

Differentiating both sides with respect to x, we get,

=> 2x = 27 (dy/dx)

=> m1 = dy/dx = 2x/27

Second curve is y2 = 8x . . . . (2)

Differentiating both sides with respect to x, we get,

=> 2y (dy/dx) = 8

=> m2 = dy/dx = 8/2y = 4/y

Solving (1) and (2), we get,

=> y4/64 = 27y

=> y (y3 − 1728) = 0

=> y = 0 or y = 12

And x = 0 or x = 18.

So, when x = 0 and y = 0

m1 = 0 and m2 = ∞

tan θ = = ∞

=> θ = π/2

So, when x = 18 and y = 12

m1 = 2x/27 = 12/9 = 4/3 and m2 = 4/y = 1/3

tan θ = => θ = tan−1 (9/13)

### (viii) x2 + y2 = 2x and y2 = x

Solution:

First curve is x2 + y2 = 2x . . . . (1)

Differentiating both sides with respect to x, we get,

=> 2x + 2y (dy/dx) = 2

=> m1 = dy/dx = (1–x)/y

Second curve is y2 = x . . . . (2)

Differentiating both sides with respect to x, we get,

=> 2y (dy/dx) = 1

=> m2 = dy/dx = 1/2y

Solving (1) and (2), we get,

=> x2 – x = 0

=> x = 0 or x = 1

And y = 0 or y = ±1.

When x = 0, y = 0, m1 = ∞ and m2 = ∞

tan θ = => θ = π/2

When x = 1 and y = ±1, m1 = 0 and m2 = 1/2

tan θ = => θ = tan−1 (1/2)

### (ix) y = 4 − x2 and y = x2

Solution:

First curve is y = 4 − x2 . . . . (1)

Differentiating both sides with respect to x, we get,

=> dy/dx = −2x

=> m1 = dy/dx = −2x

Second curve is y = x2 . . . . (2)

Differentiating both sides with respect to x, we get,

=> dy/dx = 2x

=> m= dy/dx = 2x

Solving (1) and (2), we get,

=> 2x2 = 4

=> x = ±√2

And y = 2

So, m1 = −2x = −2√2 and m2 = 2x = 2√2

tan θ = => θ = tan−1 (4√2/7)

### (i) y = x3 and 6y = 7 – x2

Solution:

First curve is y = x3 . . . . (1)

Differentiating both sides with respect to x, we get,

=> dy/dx = 3x2

=> m1 = dy/dx = 3x2

Second curve is 6y = 7 – x2 . . . . (2)

Differentiating both sides with respect to x, we get,

=> 6y (dy/dx) = – 2x

=> m2 = dy/dx = –2x/6y = – x/3y

Solving (1) and (2), we get,

=> 6y = 7 – x2

=> 6x3 + x2 – 7 = 0

As x = 1 satisfies this equation, we get x = 1 and y = 13 = 1

So, m1 = 3 and m2 = – 1/3

Two curves intersect orthogonally if m1m2 = –1

=> 3 × (–1/3) = –1

Hence proved.

### (ii) x3 – 3xy2 = – 2 and 3x2 y – y3 = 2

Solution:

First curve is x3 – 3xy2 = – 2

Differentiating both sides with respect to x, we get,

=> 3x2 – 3y2 – 6xy (dy/dx) = 0

=> m1 = dy/dx = 3(x2–y2)/6xy

Second curve is 3x2y – y3 = 2

Differentiating both sides with respect to x, we get,

=> 6xy + 3x2 (dy/dx) – 3y2 (dy/dx) = 0

=> m2 = dy/dx = –6xy/3(x2–y2)

Two curves intersect orthogonally if m1m2 = –1

=> = –1

Hence proved.

### (iii) x2 + 4y2 = 8 and x2 – 2y2 = 4.

Solution:

First curve is x2 + 4y2 = 8 . . . . (1)

Differentiating both sides with respect to x, we get,

=> 2x + 8y (dy/dx) = 0

=> m1 = dy/dx = 2x/8y = –x/4y

Second curve is x2 – 2y2 = 4 . . . . (2)

Differentiating both sides with respect to x, we get,

=> 2x – 4y (dy/dx) = 0

=> m2 = dy/dx = 2x/4y = x/2y

Solving (1) and (2), we get,

=> x = 4/√3 and y = √2/√3

So, m1 = –x/4y = –1/√2

m2 = x/2y = √2

Two curves intersect orthogonally if m1m2 = –1

=> (–1/√2) × √2 = –1

Hence proved.

### (i) x2 = 4y and 4y + x2 = 8 intersect orthogonally at (2, 1).

Solution:

First curve is x2 = 4y

Differentiating both sides with respect to x, we get,

=> 2x = 4 (dy/dx)

=> m1 = dy/dx = 2x/4 = x/2

Second curve is 4y + x2 = 8

Differentiating both sides with respect to x, we get,

=> 4 (dy/dx) + 2x = 0

=> m2 = dy/dx = −2x/4 =−x/2

For x = 2 and y = 1, we have m1 = 2/2 = 1 and m2 = −x/2 = −1.

Two curves intersect orthogonally if m1m2 = –1

=> 1 × (–1) = –1

Therefore these two curves intersect orthogonally at (2, 1).

Hence proved.

### (ii) x2 = y and x3 + 6y = 7 intersect orthogonally at (1, 1).

Solution:

First curve is x2 = y

Differentiating both sides with respect to x, we get,

=> 2x = dy/dx

=> m1 = dy/dx = 2x

Second curve is x3 + 6y = 7

Differentiating both sides with respect to x, we get,

=> 3x2 + 6 (dy/dx) = 0

=> m2 = dy/dx = −3x2/6 =−x2/2

For x = 1 and y = 1, we have m1 = 2(1) = 2 and m2 = −(1)2/2 = −1/2.

Two curves intersect orthogonally if m1m2 = –1

=> 2 × (–1/2) = –1

Therefore these two curves intersect orthogonally at (1, 1).

Hence proved.

### (iii) y2 = 8x and 2x2 + y2 = 10intersect orthogonallyat (1, 2√2).

Solution:

First curve is y2 = 8x

Differentiating both sides with respect to x, we get,

=> 2y (dy/dx) = 8

=> m1 = dy/dx = 8/2y = 4/y

Second curve is 2x2 + y= 10

Differentiating both sides with respect to x, we get,

=> 4x + 2y (dy/dx) = 0

=> m2 = dy/dx = −4x/2y =−2x/y

For x = 1 and y = 2√2, we have m1 = 4/2√2 = √2 and m2 = −2/2√2 = −1/√2

Two curves intersect orthogonally if m1m2 = –1

=> √2 × (−1/√2) = –1

Therefore these two curves intersect orthogonally at (1, 2√2).

Hence proved.

### Question 4. Show that the curves 4x = y2 and 4xy = k cut at right angles, if k2 = 512.

Solution:

First curve is 4x = y2 . . . . (1)

Differentiating both sides with respect to x, we get,

=> 2y (dy/dx) = 4

=> m1 = dy/dx = 4/2y = 2/y

Second curve is 4xy = k . . . . (2)

Differentiating both sides with respect to x, we get,

=> y + x (dy/dx) = 0

=> m2 = dy/dx = −y/x

Solving (1) and (2), we get,

=> y3 = k

=> y = k1/3

So, x = k2/3/4

As the curves intersect cut at right angles so, m1m2 = –1

=> (2/y) × (−y/x) = –1

=> 2/x = 1

=> 8/k2/3 = 1

=> k2/3 = 8

=> k2 = 512

Hence proved.

### Question 5. Show that the curves 2x = y2 and 2xy = k cut at right angles, if k2 = 8.

Solution:

First curve is 2x = y2 . . . . (1)

Differentiating both sides with respect to x, we get,

=> 2y (dy/dx) = 2

=> m1 = dy/dx = 2/2y = 1/y

Second curve is 2xy = k . . . . (2)

Differentiating both sides with respect to x, we get,

=> y + x (dy/dx) = 0

=> m2 = dy/dx = −y/x

Solving (1) and (2), we get,

=> y3 = k

=> y = k1/3

So, x = k2/3/2

As the curves intersect cut at right angles so, m1m2 = –1

=> (1/y) × (−y/x) = –1

=> 1/x = 1

=> 2/k2/3 = 1

=> k2/3 = 2

=> k2 = 8

Hence proved.

### Question 6. Prove that the curves xy = 4 and x2 + y2 = 8 touch each other.

Solution:

We have,

xy = 4 . . . . (1)

x2 + y2 = 8 . . . . (2)

Solving (1) and (2), we get,

=> (4/y)2 + y2 = 8

=> y4 − 8y2 + 16 = 0

=> (y2 − 4)2 = 0

=> y = ±2

And we get x = ±2.

Differentiating eq. (1) with respect to x, we get,

=> y + x (dy/dx) = 0

=> m1 = dy/dx = −y/x

Differentiating eq. (2) with respect to x, we get,

=> 2x + 2y (dy/dx) = 0

=> dy/dx = −x/y

At x = 2 and y = 2, we have,

m1 = −2/2 = −1 and also m2 = −2/2 = −1. Therefore m1 = m2.

Also at x = −2 and y = −2, we have m1 = m2

So, we can say that the curves touch each other at (2, 2) and (−2, −2).

Hence proved.

### Question 7. Prove that the curves y2 = 4x and x2 + y2 − 6x + 1 = 0 touch each other at the point (1, 2).

Solution:

We have,

y2 = 4x . . . . (1)

Differentiating both sides with respect to x, we get,

=> 2y (dy/dx) = 4

=> m1 = dy/dx = 2/y

Also we have,

x2 + y2 − 6x + 1 = 0 . . . . (2)

Differentiating both with respect to x, we get,

=> 2x + 2y (dy/dx) − 6 = 0

=> m2 = dy/dx = (6−2x)/2y = (3−x)/y

At x = 1 and y = 2, we have,

m1 = 2/2 = 1

m2 = (3−1)/2 = 1.

As m1 = m2, we can say that the curves touch each other at (1, 2).

Hence proved.

### (i) x2/a2 − y2/b2 = 1 and xy = c2

Solution:

We have,

x2/a2 − y2/b2 = 1

Differentiating both sides with respect to x, we get,

=> 2x/a2 − (2y/b2) (dy/dx) = 0

=> m1 = dy/dx = b2x/a2y

Also, xy = c2

Differentiating both sides with respect to x, we get,

=> y + x (dy/dx) = 0

=> m2 = dy/dx = −y/x

For curves to intersect orthogonally, m1 m2 = −1.

=> (b2x/a2y) (−y/x) = −1

=> a2 = b2

Therefore, a2 = b2 is the condition for the curves to intersect orthogonally.

### (ii) x2/a2 + y2/b2 = 1 and x2/A2 − y2/B2 = 1

Solution:

We have,

x2/a2 + y2/b2 = 1 . . . . (1)

Differentiating both sides with respect to x, we get,

=> 2x/a2 + (2y/b2) (dy/dx) = 0

=> m1 = dy/dx = −b2x/a2y

Also, x2/A2 − y2/B2 = 1 . . . . (2)

=> 2x/A2 − (2y/B2) (dy/dx) = 0

=> m2 = dy/dx = B2x/A2y

For curves to intersect orthogonally, m1 m2 = −1.

=> (−b2x/a2y) (B2x/A2y) = −1

=> x2/y2 = a2A2/b2B2 . . . . (3)

Subtracting (2) from (1) gives,

=> => Putting this value in (3), we get,

=> => B2 + b2 = a2 − A2

=> a2 − b2 = A2 + B2

Therefore, a2 − b2 = A2 + B2 is the condition for the curves to intersect orthogonally.

### Question 9. Show that the curves and intersect at right angles.

Solution:

We have, . . . . (1)

Differentiating both sides with respect to x, we get,

=> 2x/(a2 + λ1) + 2y/(b2 + λ1) (dy/dx) = 0

=> m1 = dy/dx = Also we have, . . . . (2)

Differentiating both sides with respect to x, we get,

=> 2x/(a2 + λ2) + 2y/(b2 + λ2) (dy/dx) = 0

=> m2 = dy/dx = For curves to intersect orthogonally, m1 m2 = −1.

=> => . . . . (3)

Subtracting (2) from (1) gives,

=> => Putting this value in (3), we get,

=> => m1m2 = −1

Hence proved.

### Question 10. If the straight line x cos α + y sin α = p touches the curve x2/a2 − y2/b2 = 1, then prove that a2 cos2α − b2 sin2α = p2.

Solution:

Suppose (x1, y1) is the point where the straight line x cos α + y sin α = p touches the curve

x2/a2 − y2/b2 = 1.

Now equation of tangent to x2/a2 − y2/b2 = 1 at (x1, y1) will be,

=> Therefore, the equation and the straight line x cos α + y sin α = p represent the same line. So, we get,

=> => x1 = a(cos α)/p and x2 = b(sin α)/p . . . . (1)

Now the point (x1, y1) lies on the curve x2/a2 − y2/b2 = 1.

=> Using (1), we get,

=> => a2 cos2α − b2 sin2α = p2

Hence proved.

I think you got complete solutions for this chapter. If You have any queries regarding this chapter, please comment in the below section our subject teacher will answer you. We tried our best to give complete solutions so you got good marks in your exam.

If these solutions have helped you, you can also share rdsharmasolutions.in to your friends.